2016
DOI: 10.1016/j.vetmic.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Two-way antigenic cross-reactivity between porcine epidemic diarrhea virus and porcine deltacoronavirus

Abstract: Porcine epidemic diarrhea virus (PEDV) and porcine deltacoronavirus (PdCV) cause indistinguishable clinical signs and pathological changes in swine. Here we investigated the antigenic relationship between PEDV and PdCV. We provide the first evidence that conserved epitope(s) on the respective viral nucleocapsid proteins cross-react with each other although virus neutralization cross-reactivity was not observed. As a practical matter, prevention of these two very similar diseases of swine will require the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
1
45
0
Order By: Relevance
“…Therefore, the eukaryotic-expressed S1 protein is likely more advantageous than the WV as the antigen for PEDV serological assays. For another two major structural proteins M and N, due to common epitopes shared by PEDV, TGEV and PDCoV, several studies have previously demonstrated that PEDV M or N presented some cross-reactivity to TGEV or PDCoV (Gimenez-Lirola et al, 2017;Lin et al, 2015;Ma et al, 2016). In contrast, recombinant PEDV-S1 had no cross-reactivity with sera from these porcine coronaviruses, showing the best diagnostic sensitivity (Gimenez-Lirola et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the eukaryotic-expressed S1 protein is likely more advantageous than the WV as the antigen for PEDV serological assays. For another two major structural proteins M and N, due to common epitopes shared by PEDV, TGEV and PDCoV, several studies have previously demonstrated that PEDV M or N presented some cross-reactivity to TGEV or PDCoV (Gimenez-Lirola et al, 2017;Lin et al, 2015;Ma et al, 2016). In contrast, recombinant PEDV-S1 had no cross-reactivity with sera from these porcine coronaviruses, showing the best diagnostic sensitivity (Gimenez-Lirola et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although several standard detection methods, for example virus isolation, virus neutralization tests, and indirect immunofluorescence assay, are available for the detection of viruses, these techniques are time‐consuming and not suitable for detecting large‐scale samples. Currently, polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA) methods for the detection of these viruses have been reported (Luo et al, ; Ma et al, ; Zhu, Wang, Cui, & Cui, ). Due to the high pathogenicity of these viruses to suckling piglets, which have immature immune systems and few antibodies, ELISA is inefficient for detecting these viruses compared to PCR.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recently antigenic cross-reactivity between PDCoV Michigan strain and PEDV, mediated by N protein, has been detected using a monoclonal antibody specific for N protein. Nevertheless, no cross-neutralization has been detected between these strains (Ma et al, 2016).…”
Section: Porcine Delta Coronavirus (Pdcov)mentioning
confidence: 92%
“…Chinese ferret-badger that were positive in 2.4% of and 1.1% of the animals tested, respectively Ma et al, 2015;Wang et al, 2014a).Phylogenetic analysis of PDCoV S gene nucleotide sequence illustrates the close relationship between PDCoV, delta-CoVs of small mammals, avian-delta CoVs, and alpha-CoVs (Fig. 7) (Hu et al, 2015).…”
Section: Porcine Delta Coronavirus (Pdcov)mentioning
confidence: 95%
See 1 more Smart Citation